2019
DOI: 10.1186/s12984-019-0614-9
|View full text |Cite
|
Sign up to set email alerts
|

Pathway-specific modulatory effects of neuromuscular electrical stimulation during pedaling in chronic stroke survivors

Abstract: BackgroundNeuromuscular electrical stimulation (NMES) is extensively used in stroke motor rehabilitation. How it promotes motor recovery remains only partially understood. NMES could change muscular properties, produce altered sensory inputs, and modulate fluctuations of cortical activities; but the potential contribution from cortico-muscular couplings during NMES synchronized with dynamic movement has rarely been discussed.MethodWe investigated cortico-muscular interactions during passive, active, and NMES r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 77 publications
0
27
0
Order By: Relevance
“…Furthermore, if this is the case, it may provide a rationale for designing interventions targeting each fundamental muscle synergy with simple tasks before practicing complex tasks at the beginning of rehabilitation. Potential interventions include muscle synergy-based approaches using functional electrical stimulations to optimize the structure of fundamental synergies and temporal recruitments to improve motor performance in stroke [55][56][57][58]. Lastly, we found that different tasks with various biomechanical demands and constraints may largely share the same muscle synergies with different combinations of synergies to be merged.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, if this is the case, it may provide a rationale for designing interventions targeting each fundamental muscle synergy with simple tasks before practicing complex tasks at the beginning of rehabilitation. Potential interventions include muscle synergy-based approaches using functional electrical stimulations to optimize the structure of fundamental synergies and temporal recruitments to improve motor performance in stroke [55][56][57][58]. Lastly, we found that different tasks with various biomechanical demands and constraints may largely share the same muscle synergies with different combinations of synergies to be merged.…”
Section: Discussionmentioning
confidence: 81%
“…The distribution of papers in the categories is shown in a pie chart in Figure 4. Study of the cortico-muscular coupling (1) during motor tasks [37][38][39][40][41] and (2) with electrical stimulation [42][43][44][45][46] Investigation of the effects of exoskeleton on functional connectivity [47][48][49] Investigation of the effects of visual feedback [50,51] Detection of movement intention [52,53] Study of the interhemispheric interaction with TMS [54] Study of a neurophysiological marker of stress [55] Study of slow cortical potentials in stroke [56] Study of correlation between lower back pain and altered postural stabilization [57] Test new rehabilitation paradigm [34,[58][59][60][61][62] Investigation of the efficacy of BMI [63] and EEG feedback [64] Table 1. Type of study and aim.…”
Section: Type Of Studymentioning
confidence: 99%
“…An aim commonly found in these works was the assessment of the cortico-muscular coupling during movements [37][38][39][40][41] as a method to better understand motor control mechanisms for improving the rehabilitation design. Cortico-muscular coherence was also tested as a tool for investigating the effects of functional electrical stimulation [42][43][44][45][46]. Some studies analyzed the effects of treatments based on exoskeletons on neuromotor outcomes [47][48][49].…”
Section: Type Of Study Aimmentioning
confidence: 99%
See 1 more Smart Citation
“…100 Moreover, interaction of NMES in dynamic movements could facilitate understanding of post-stroke motor rehabilitation mechanisms in the physical world, and foster to its wide applications in stroke survivors. 118 Previous studies primarily used standardized stimulation settings. It is necessary to investigate more optimized NMES paradigms considering muscle/cortical responses in different motor tasks and subjects.…”
Section: Neuromuscular Electrical Stimulationmentioning
confidence: 99%